Vibration modelling and analysis of piezoelectric energy harvesters - Mak, Kuok Hang (2011)
The performance of piezoelectric cantilever beam energy harvesters subjected to base excitation is considered in this work. Based on the linear assumption, a theoretical model is developed to predict the mechanical and electrical responses of the harvester and in comparison to other theoretical models, more accurate mode shape functions are used for the structural part of the harvester. The model is validated against experimental measurements and parameter studies are carried out to investigate the maximum power output in different situations.